2017
DOI: 10.1016/j.rboe.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of cementation technique using polished, conical, triple-tapered femoral stem in hip arthroplasty

Abstract: ObjectiveTo radiographically evaluate the quality of cementation and implantation technique using a polished, triple-tapered femoral stem in total hip arthroplasty (THA).MethodRetrospective study with radiographic evaluation of 86 hips in 83 patients who underwent to primary THA with the triple-tapered cemented femoral stem C-Stem (DePuy Orthopedics, Warsaw, Indiana). Cases with at least one-year of follow-up were included, and data related to preoperative, immediate postoperative, and late postoperative radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Leunig et al reported satisfactory component positioning in bikini anterior THA with cementation at 4 years post-operative, although this cementation was used in only 24 of 964 cases [ 5 ]. Schuroff et al conducted a radiographic evaluation of cementation using a posterolateral surgical approach [ 22 ]. Compared to their results we identified a higher percentage of Barracks cementation type A and B in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Leunig et al reported satisfactory component positioning in bikini anterior THA with cementation at 4 years post-operative, although this cementation was used in only 24 of 964 cases [ 5 ]. Schuroff et al conducted a radiographic evaluation of cementation using a posterolateral surgical approach [ 22 ]. Compared to their results we identified a higher percentage of Barracks cementation type A and B in our series.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 91.5% was inserted in neutral position, and the CMK stem that was also implanted with line-to-line cementing technique, was in a neutral position in 80.5% [ 15 ]. In contrast, 65.3% was inserted within 2 degrees of varus or valgus in the Exeter stem [ 24 ], and 61.7% was in a neutral position in the C-stem [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most studies using a different type of implants and approaches, Barrack Type B cementation was the most prevalent [34]. Using the C-stem (DePuy Synthes, Warsaw, Indiana) and posterior approach, Schuroff et al [10] reported 5.8% type A, 53,5% type B, 31.4% type C, and 9.3% type D quality of cement mantle in 86 hips according to the Barrack classification. Ek and Choong [35] using the same stem reported 46% type B, 45.7% type A, and 8% type C cement mantles.…”
Section: Tablementioning
confidence: 99%
“…The limited literature available suggests the DAA is probably related to a higher rate of deficiency of the cement mantle compared with the posterior approach [ 9 ]. However, the cement mantle quality is recognized as being highly associated with the longevity of a prosthesis [ 9 , 10 ]. Although some degree of uncertainty still exists, the initial thickness and homogeneity of the cement mantle, as well as the presence of deficiencies, are critical in the process of aseptic loosening [ 11 ].…”
Section: Introductionmentioning
confidence: 99%